Angiosarcoma in the mandible: Report of a rare case - Shirin Vashishth; M Srinivasa Raju; Satheesha Reddy; G N Suma; S M Raviprakash; N N Singh (Wolters Kluwer Medknow Publications, 2008)
Angiosarcoma in the oral cavity, pharynx, or paranasal sinuses comprises less than 5% of the total cases of neoplasms. Age of presentation varies from 1 day to 67 years. Intraorally, the most preferred site is the mandible and the least common is the maxilla. Histologically, all angiosarcomas show a wide spectrum of differentiation of endothelial cells. Treatment is surgery in combination with radiation therapy. However, the prognosis for patients is generally poor, with one half of the patients dying within 15 months of diagnosis. Here is a rare case of angiosarcoma of the body of the mandible reported in an 80-year-old male patient.